What diagnostic testing, if any, is needed in pregnant women with asymptomatic elevated urobilinogen?. Issue 4 (April 2017) - Pons, Lara
Abstract : EVIDENCE‐BASED ANSWER : Urine urobilinogen during pregnancy is not associated with hemolysis disorders (SOR: C, observational study). It has a low positive likelihood ratio for the detection of abnormal bilirubin and liver function tests (SOR: C, observational study extrapolated from nonpregnant patients).